Technology Entrepreneurship (ENT600) Analysis on laundry service / Abdul Zahier Ismail, Muhammad Syafiq khusairi and Mohamad Nizar Mohd Naim. - Ismail, Abdul Zahier; khusairi, Muhammad Syafiq; Mohd Naim, Mohamad Nizar
The team has decided to build a training kit that would help workers and students to improve their skills in electrical wiring system to repair breakdown machines. The training kit have a pneumatic and programmable logic controller (PLC) system that help consumer in electrical wiring issue by troubleshooting problems with the machine. The product would be available for factories and universities in Malaysia.